Storytelling in the digital world - De Fina, Anna; Perrino, Sabina (Benjamins current topics, 2019)
Storytelling in the Digital World' explores new, emerging narrative practices as they are enacted on digital platforms such as Amazon, Facebook, Twitter, and YouTube. Contributors' online ethnographies investigate a wide range of themes including the nature of processes of transformation and recontextualization of offline events into digital narratives; the effects of digital anonymity and pseudonymity on narrative practices; the strategies through which virtual communities discursively work together to solidify and negotiate their sociocultural identities; the tensions between the affordances that characterize different online media and the communicative needs of users; the structures and modes in which virtual users construct and enact participatory practices in these environments; and the significance of different spatiotemporal dimensions in the encoding, sharing and appreciation of stories. More generally, the volume engages with some of the theoretical and methodological challenges that the growing presence of digital technologies and media poses to narrative analysis. 0Originally published as special issue of 'Narrative Inquiry' 27:2 (2017).